2018
DOI: 10.1071/rd16441
|View full text |Cite
|
Sign up to set email alerts
|

Expanded equine cumulus–oocyte complexes exhibit higher meiotic competence and lower glucose consumption than compact cumulus–oocyte complexes

Abstract: Expanded equine cumulus-oocyte complexes exhibit higher meiotic competence and lower glucose 1 consumption than compact cumulus-oocyte complexes To test this 24 hypothesis eCOCs, cCOCs, and expanded or compact mural granulosa cells (EC and CC respectively) were 25 matured in vitro for 30 hours and the maturation rate, glucose metabolism, and expression of genes involved in 26 glucose transport, glycolysis, apoptosis and meiotic competence were determined. Significant differences were 27 found between eCOCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Bovine cumulus responded to hypoxia during IVM through upregulation of GLUT1 gene expression (Slc2a1), and HIF1α seems to play a role in mediating this response [64]. For equine cumulus cells, the expression of the GLUT1 gene (Slc2a1) was previously documented, with significantly higher abundance in expanded CC than in compact cumulus cells [71]. These studies corroborate the observed GLUT1 underrepresentation after maturation under the hyperoxic (20%) in vitro condition in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Bovine cumulus responded to hypoxia during IVM through upregulation of GLUT1 gene expression (Slc2a1), and HIF1α seems to play a role in mediating this response [64]. For equine cumulus cells, the expression of the GLUT1 gene (Slc2a1) was previously documented, with significantly higher abundance in expanded CC than in compact cumulus cells [71]. These studies corroborate the observed GLUT1 underrepresentation after maturation under the hyperoxic (20%) in vitro condition in this study.…”
Section: Discussionsupporting
confidence: 88%
“…These COCs also exhibited higher maturational competence (50% versus 21.7%). These expanded COCs showed significantly lower glucose consumption along with decreased pyruvate and lactate production [71].…”
Section: Discussionmentioning
confidence: 99%
“…Poly (A) RNA was extracted using the Dynabeads ® mRNA DIRECT™ Micro Kit (Ambion ® ; Thermo Fisher Scientific Inc., Oslo, Norway) following the manufacturer's instructions with minor modifications (González‐Fernández et al, ). After 10 min of incubation in lysis buffer with Dynabeads, poly (A) RNA attached to the Dynabeads was extracted with a magnet and washed twice in washing buffer A and washing buffer B. RNA was eluted with Tris‐HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Transport was performed at 15°C within 8 hours of slaughter. Immature cumulus‐oocyte complexes (COCs) were obtained by follicular scraping as previously described 19 using TCM199 supplemented with HEPES, 1 mg/mL BSA, 10 µg/mL heparin and 2.2 g/L bicarbonate. The oocytes (n = 641) were collected and maintained in holding medium (HM, TCM199 supplemented with HEPES + 20% fetal calf serum (FCS) + 0.5% gentamycin) for a maximum of 12 hours at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%